2021
DOI: 10.1021/acs.jpca.1c06678
|View full text |Cite
|
Sign up to set email alerts
|

How Is the Oxidation Related to the Tautomerization in Vitamin B9?

Abstract: The relationship between the lactim−lactam tautomerization and the free-radical scavenging reaction in vitamin B9 [folic acid (FA)] was investigated by density functional theory calculations. 6-Methylpterin was also adopted for the detailed analyses of various reaction paths. For pterin, the transition state of the tautomerization with two water molecules (n = 2) was calculated to be of the lowest activation energy. The protontransfer circuit of n = 2 is retained (not broken) even with the addition of outer wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It is suggested that the unfavored lactim isomer can undergo oxidation and possibly provide insight into the antioxidant properties of folate [ 64 ]. DFT calculations were performed on 6-methylpterin as an analogue for FA to find the connection between lactam/lactim tautomerization and oxidation [ 65 ]. The transition state (TS) between lactim and lactam isomers was calculated to show that two intervening water molecules are required to afford the lowest activation energy for the tautomerization.…”
Section: Computational Studiesmentioning
confidence: 99%
“…It is suggested that the unfavored lactim isomer can undergo oxidation and possibly provide insight into the antioxidant properties of folate [ 64 ]. DFT calculations were performed on 6-methylpterin as an analogue for FA to find the connection between lactam/lactim tautomerization and oxidation [ 65 ]. The transition state (TS) between lactim and lactam isomers was calculated to show that two intervening water molecules are required to afford the lowest activation energy for the tautomerization.…”
Section: Computational Studiesmentioning
confidence: 99%